2018
DOI: 10.1039/c7ra13295f
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic β-glucosidase inhibition and renal blood flow suppression are leading causes for the enhanced systemic exposure of salidroside in hypoxic rats

Abstract: CBG inhibition and renal blood flow suppression are leading causes for the enhanced systemic exposure of SAL in hypoxic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Studies have shown that RC may synergistically inhibit myocardial apoptosis and improve MI-reperfusion injury through the anti-inflammatory regulation of energy metabolism and oxidative stress, which may be related to the HIF-1/VEGF/PI3K-Akt signaling pathway [32]. Further research found that the systemic exposure to salidroside in hypoxia increased significantly, which may be related to the weakening of liver metabolism under the disease state [33]. This conclusion is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that RC may synergistically inhibit myocardial apoptosis and improve MI-reperfusion injury through the anti-inflammatory regulation of energy metabolism and oxidative stress, which may be related to the HIF-1/VEGF/PI3K-Akt signaling pathway [32]. Further research found that the systemic exposure to salidroside in hypoxia increased significantly, which may be related to the weakening of liver metabolism under the disease state [33]. This conclusion is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…We believe that salidroside directly reaches the lesion site when interfering with colitis by gavage. Moreover, DSS‐induced intestinal barrier breakdown may result in higher plasma concentration (Chang, Yao, Hsieh, Lu, & Yeh, 2007; Qi et al, 2018). Combined with the dual effect of salidroside on the intestinal flora, a small dose may achieve a suitable therapeutic effect on gastrointestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse intestinal S9 was prepared, according to the method reported. , The incubation system was composed of intestinal S9 (2.0 mg protein/mL), MgCl 2 (3.2 mM), MLT (100 μM), and GCL (20 mM) or TCA (1.0 mM) , in 100 μL of phosphate-buffered saline (PBS, 0.1 M, pH 7.4) fortified with capture agents GSH (200 μM) or NAC (2.0 mM). Control incubation groups lacked GCL or TCA.…”
Section: Experimental Proceduresmentioning
confidence: 99%